Assessing health impacts of an environmental pan-African development project: A migration perspective. (August 2020) - Duboz, Priscilla; Boëtsch, Gilles; Guisse, Aliou; Macia, Enguerran
Abstract: The general objective of this article is to analyze to what extent the implementation of the Great Green Wall project is likely to disrupt migratory movements towards the rural environment and, consequently, the socio-economic structures and health status of local populations. This study was carried out in 2015 on a population sample of 500 individuals living in the municipality of Tessekere, constructed using the quota method. Socioeconomic and demographic characteristics, migratory status and self-rated health of individuals were collected during face-to-face interviews. Statistical analyses used were Chi-square tests, student and binary logistic regressions. Results show that internal migrants in the municipality of Tessekere represent 13.40% of the study population. Migrants more often work as civil servants, artisans, craft workers or traders than the region's native population, who are generally livestock breeders or jobless. While place of birth does not play a significant role, it appears that the length of residence of migrants in rural areas influences health status: migrants residing in the municipality of Tessekere for less than 10 years are less likely to report poor health, regardless of their sex, age, occupation, material well-being and perceived stress. In conclusion, an environmental requirement (combating desertification), addressed by an international political project - the Great Green Wall - and then applied at the national level, has transformed the demographic, economic and health structure of a local population. In conclusion, our study showed that (1) an examination of migration can offer a means of interpreting the impact of development projects and the local changes they entail, and (2) migration is a unique prism through which one can study how exposure to a new physical and social environment influences the health of populations. Highlights: The Great Green Wall project has provoked a migratory movement towards a rural area. Previously landlocked, this area now has a high rate of immigration. These urban-rural migrations create an original socio-economic population profile. As a result, the health of this rural population is also altered.